C14 Striatal Magnetic Resonance Spectroscopy of Transgenic HD Minipigs. (17th September 2014) - Frank, F; Nagelmann, N; Liebsch, L; Schubert, R; Wirsig, M; Schramke, S; Schuldenzucker, V; Marcegaglia, M; Ott, S; Hölzner, E; Faber, C; Reilmann, R
Abstract : Background: Our study is the first phenotyping study on TgHD minipigs from the Institute of Animal Physiology and Genetics in Libéchov (Czech Republic). MRI scans including anatomical, diffusion-weighted and spectroscopic sequences were performed to assess anatomical and metabolic changes in the brain. Proton Magnetic Resonance Spectroscopy (MRS) is a validated method for determining changes in the relative molecule concentration in HD patients and in TgHD mice. Aims: For determining relative molecule concentrations in the striatum of the tgHD and wildtype minipigs we performed a baseline and a follow-up assessment. Feasibility and tolerability same as between group differences and longitudinal changes will be assessed. Methods/techniques: The minipigs were scanned on a 3T Philips Achieva system at baseline and at one year follow-up. Single-voxel based spectroscopy (PRESS) of the striatum on the right and left hemisphere was acquired using the following parameters: TR: 2000 ms, TE: 32 ms, measured voxel size: 8 × 22 × 8mm, averages: 176, scan duration: 6 min. The concentration of N-Acetylasparate, myo-inositol, glutamate and glutamine relative to creatine was calculated by LCModel. Results/outcome: In the data collected to date no significant differences were seen between the transgenic and the wildtype group at MRI 1 (baseline-6 month of age) and 2 (18 months of age). The spectra showed well-resolved lines of the major metabolites, which were observed at similar relative concentrations as expected for humans. The statistical analysis is pending and will be presented at the EHDN meeting. Conclusions: In this pilot study cross-sectional baseline and longitudinal data from tgHD minipigs and controls was successfully acquired. Thus longitudinal changes between transgenic and wildtype may be expected later on due to the slowly progressive nature of HD. Acknowledgement: Funded by the CHDI Foundation